Finding the Balance in Online Library Instruction: Sustainable and Personal. Issue 1 (2nd January 2017) - Moran, Carrie; Mulvihill, Rachel
ABSTRACT: The UCF Libraries are continually developing new forms of library instruction to meet the needs of a growing student body with the same number of librarians. These efforts attempt to find the balance between impersonal online tutorials and time-intensive embedded librarianship. The pros and cons of each model employed at our growing university are discussed, along with strategies to identify and implement sustainable library instruction in an academic library.